Perancangan Aplikasi penjualan Sepeda pada Toko Eco Bike Berbasis Web Menggunakan Metode Waterfall - Asnawi, Asnawi; M. Irfan (Yayasan Literasi Sains Indonesia, 2022)
Ecobike shop is a shop that provides and sells sport bikes and bicycle accessories products. The Ecobike shop has recently experienced some difficulties in developing sales and promotions, because the Ecobike shop still uses a sales and promotion system that is still conventional in the sense that customers still have to come to the store's sales location directly to see the condition of the bicycle product and a promotion system that only spreads brochures to customers, although it has been running well in the city of Medan but this is not optimal for today. The method applied in the eco bike sales application uses a descriptive method approach to collect the information data needed in order to be able to make a picture of the situation, event, or trend that is developing at this time.